METHODOLOGY FOR DESIGNING AND IMPLEMENTING INTEGRATED DIGITAL EDUCATIONAL AND METHODOLOGICAL COMPLEXES IN PEDAGOGICAL HIGHER EDUCATION - Nodir Quljonov (Bright Mind Publishing, 2025)
This article explores the methodological foundations for designing and implementing integrated digital instructional-methodological complexes (IDIMC) in higher pedagogical education. It highlights the structure of digital complexes, their didactic potential, and the stages of their effective integration into the educational process. Based on experimental results, the study demonstrates the impact of such digital solutions on education quality and student engagement.
Keywords: Digital education, instructional-methodological complex, integration, didactic tool, methodology, innovative technology.